2021
DOI: 10.1159/000516853
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Online Psychoactive Substance Trade via Telegram during the COVID-19 Pandemic

Abstract: <b><i>Background:</i></b> In this article, we present an evaluation of online psychoactive substance trade via Telegram, a free encrypted social media messenger service. The evaluation took place during the COVID-19 pandemic, which allowed us to monitor the effects of the spring 2020 lockdown in the Netherlands on substance trade via Telegram. <b><i>Objective:</i></b> The objective of this study was to evaluate whether changes in psychoactive substance trade on T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Discord drug servers bear similarities to Facebook drug selling groups (Demant et al, 2019), or group chats on messaging platforms such as Telegram (Blankers et al, 2021), which enable similarly competitive selling environments and are typically also “managed” by a group “administrator” who grants access to new members, and where membership of many different selling groups is also commonplace (Demant et al, 2019). Bakken and Demant have termed groups such as these “public digital markets” by virtue of their typically high levels of openness and ease of access (Bakken & Demant, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discord drug servers bear similarities to Facebook drug selling groups (Demant et al, 2019), or group chats on messaging platforms such as Telegram (Blankers et al, 2021), which enable similarly competitive selling environments and are typically also “managed” by a group “administrator” who grants access to new members, and where membership of many different selling groups is also commonplace (Demant et al, 2019). Bakken and Demant have termed groups such as these “public digital markets” by virtue of their typically high levels of openness and ease of access (Bakken & Demant, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have focused on the use of popular, mainstream social media platforms such as Facebook, Snapchat, Instagram, Whatsapp, and encrypted chat apps like Wickr and Telegram (Bakken, 2020; Blankers et al, 2021; Demant et al, 2020; Demant et al, 2019; Moyle et al, 2019). Understanding of how lesser-known social media platforms may facilitate the buying and selling of illegal drugs remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, other important changes in the digital media and communications landscape were occurring. Messaging apps, in particular those that offered encrypted messaging services and real-time mobile group messaging (Baulch et al, 2020;Ling, 2017;Nobari et al, 2021), as well as social media services that facilitated interaction and the sharing of user-generated content (McCay-Peet and Quan-Haase, 2016), afforded new possibilities for drug trading (Blankers et al, 2021;Childs et al, 2021;Demant et al, 2019;Li et al, 2019;McCulloch and Furlong, 2019;Moyle et al, 2019;Oksanen et al, 2021;Shah et al, 2021;van der Sanden et al, 2021), alongside the dramatic rise in social media use (Auxier and Anderson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…App-mediated drug trading may include joining broadcast-type groups or following public profiles of drug sellers, then using one-toone messaging to broker a deal, followed by an in-person exchange or postal delivery (Li et al, 2019;McCulloch and Furlong, 2019;Moyle et al, 2019). Public data from app-mediated drug selling groups have been assessed across multiple platforms (e.g., Telegram (Blankers et al, 2021) and Instagram (Li et al, 2019;Shah et al, 2021)), with these studies confirming seller advertisement posts predominate with buyers directed to encrypted chat apps for purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 pandemic and the disruptions it presented for the work of drug policy research and activism, we observed national lockdowns impacting patterns of drug use, and then how quickly they returned to "normal" when public health measures were eased (EMCDDA, 2021;Chang et al, 2020). Some drug market monitoring studies provided evidence of disruption to drug cryptomarkets (Bergeron et al, 2020) and changes in illicit drug offerings on social media (Blankers et al, 2021), but we also learntyet againthat drug supply networks remained resilient during the pandemic (EMCDDA, 2021;Scherbaum et al, 2021). Challenged by social distancing measures and resource constraints, harm reduction and professional drug services responded by implementing innovative modes of service delivery, including telemedicine, home-delivery and contactless opioid substitution treatment (EMCDDA, 2020;Tyndall, 2020).…”
mentioning
confidence: 98%